2-Methylquinazoline derivative 23BB as a highly selective histone deacetylase 6 inhibitor alleviated cisplatin-induced acute kidney injury. Issue 1 (17th January 2020) - Hao, Yan; Guo, Fan; Huang, Zhuo; Feng, Yuying; Xia, Zijing; Liu, Jing; Li, Lingzhi; Huang, Rongshuang; Lin, Lin; Ma, Liang; Fu, Ping
Abstract: Histone deacetylases 6 (HDAC6) has been reported to be involved in the pathogenesis of cisplatin-induced acute kidney injury (AKI). Selective inhibition of HDAC6 might be a potential treatment for AKI. In our previous study, a highly selective HDAC6 inhibitor (HDAC6i) 23BB effectively protected against rhabdomyolysis-induced AKI with good safety. However, whether 23BB possessed favorable renoprotection against cisplatin-induced AKI and the involved mechanisms remained unknown. In the study, cisplatin-injected mice developed severe AKI symptom as indicated by acute kidney dysfunction and pathological changes, companied by the overexpression of HDAC6 in tubular epithelial cells. Pharmacological inhibition of HDAC6 by the treatment of 23BB significantly attenuated sCr, BUN and renal tubular damage. Mechanistically, 23BB enhanced the acetylation of histone H3 to reduce the HDAC6 activity. Cisplatin-induced AKI triggered multiple signal mediators of endoplasmic reticulum (ER) stress including PERK, ATF6 and IRE1 pathway, as well as CHOP, GRP78, p-JNK and caspase 12 proteins. Oral administration of our HDAC6i 23BB at a dose of 40 mg/kg/d for 3 days notably improved above-mentioned responses in the injured kidney tissues. HDAC6 inhibition also reduced the number of TUNEL-positive tubular cells and regulated apoptosis-related protein expression. Overall, these data highlighted that HDAC6 inhibitor 23BB modulated apoptosis via the inhibition of ER stress in the tubular epithelial cells of cisplatin-induced AKI.